Manajemen Komunikasi dalam Pelayanan Penerbitan Sertifikat Tanah di Kantor Pertanahan Kota Administrasi Jakarta Pusat - Putri, Ranti Dwi; Ningsih, Sari; Setyawati, Kiki (PANDITA: Interdisciplinary Journal of Public Affairs, 2024)
This research will focus on service communication, factors that support and inhibit services as well as the effectiveness of land certificate issuance service communication at the Central Jakarta City Administration Land Office. There were 7 informants who were sources in this research. Data collection techniques were carried out using library research and field research. This aims to make it easier for service users to access service information available at the Central Jakarta City Administration Land Office. (2) Factors that support land certificate issuance services at the Central Jakarta City Administration Land Office, include: the existence of regulations that make it easier, the availability of qualified human resources and personnel with integrity, the existence of technology that helps make work easier, and reform of the public service bureaucracy. implemented to reduce service time to be shorter. (3) Obstacles that are still encountered in land certificate issuance services at the Central Jakarta City Administration Land Office, namely: the status of the land is still in dispute, meaning that the issuance of land certificates must wait for legal certainty regarding the ownership of the land in question, incomplete land archives or documents, public ignorance In fulfilling the requirements for issuing land certificates, computer facilities to support public services sometimes experience errors so that service activities become hampered, and there are a handful of service officers who do not understand service SOPs. (4) The effectiveness of public services in issuing land certificates at the Central Jakarta City Administration Land Office still needs to be improved. For this reason, we have carried out various innovations through the Julapat Program (7 Quick Services) and the Landing Service, which is a service for people who do not have time to take care of land documents on weekdays and can take care of them on weekends. Apart from that, the Central Jakarta City Administration Land Office also continues to serve applicants during break times. This program aims to get closer to applicants directly and show service users that managing services is simple and cheap.